Intertextuality in Lain Singh Bangdel's Paintings (SIRJANĀ – A Journal Of Arts and Art Education, 2024)
Intertexuality refers to the art of involving two or more than two artistic and literary texts as a single composition of art. Western modernist technique, particularly with the style of Pablo Picasso of paintings, Nepali architecture, and socio-cultural literature based on Nepali subject matter are the key intertexuality in Bangdel's paintings, which makes his works more influential in Nepali contemporary art. The main purpose of this paper is to explore the notion of intertexuality in Bangdel's work. This study is qualitative in nature, where ideas of intertexuality have been revealed and some paintings created by Bangdel are analyzed and discussed on the basis of various primary and secondary sources.